Hypothalamic Neurochemical Changes in Long-Term Recovered Bilateral Subdiaphragmatic Vagotomized Rats - Anna Teresa Kobrzycka; Adrian Mateusz Stankiewicz; Joanna Goscik; Monika Gora; Beata Burzynska; Roksana Iwanicka-Nowicka; Roksana Iwanicka-Nowicka; Krystyna Pierzchala-Koziec; Marek Wieczorek (Frontiers in Behavioral Neuroscience, 2022)
BackgroundVagus nerve is one of the crucial routes in communication between the immune and central nervous systems. The impaired vagal nerve function may intensify peripheral inflammatory processes. This effect subsides along with prolonged recovery after permanent nerve injury. One of the results of such compensation is a normalized plasma concentration of stress hormone corticosterone – a marker of hypothalamic-pituitary-adrenal (HPA) axis activity. In this work, we strive to explain this corticosterone normalization by studying the mechanisms responsible for compensation-related neurochemical alterations in the hypothalamus.Materials and MethodsUsing microarrays and high performance liquid chromatography (HPLC), we measured genome-wide gene expression and major amino acid neurotransmitters content in the hypothalamus of bilaterally vagotomized rats, 1 month after surgery.ResultsOur results show that, in the long term, vagotomy affects hypothalamic amino acids concentration but not mRNA expression of tested genes.DiscussionWe propose an alternative pathway of immune to CNS communication after vagotomy, leading to activation of the HPA axis, by influencing central amino acids and subsequent monoaminergic neurotransmission.